Kearifan Lokal Tentang Komitmen untuk Mengasihi dan Melayani Tuhan - Kilian Sirait (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
Local wisdom refers to the cultural values ​​and norms that regulate people's daily lives. These values ​​and norms, which are ingrained and considered correct, guide the behavior of the local community. God's servants are individuals chosen and appointed by God to serve His people. Willingness to serve, loyalty in carrying out service, and no discrimination in serving others are manifestations of the commitment and motivation that exist within the servant. The aim of this research is to provide an overview of local wisdom related to commitment to love and devotion to God. To achieve this goal, a qualitative descriptive approach was used, which includes describing a commitment to love God, understanding God's work throughout history, and exploring its practical applications. The research methodology includes a thorough review of relevant literature and Biblical texts to gather comprehensive information. The findings of this research reveal that commitment to God is a fundamental aspect of local wisdom. By continuing to obey His commandments, Christians can protect themselves from the effects of their current circumstances. Therefore, the findings of this research emphasize the need for unwavering faith and obedience in upholding our devotion as a community in worship.